La última batalla de un guerrillero conservador: Juan Chávez (1868) (Tzintzun, Revista de Estudios Históricos, 2019)
In this article I attempt to describe the final year (1868) of the carrier of theimperialist and conservative Juan Chávez â€”today transformed in a social bandit by local tradition and collective memoryâ€” against the forces of the liberal government in the state of Aguascalientes. Through this I seek to clarify some relevant aspects of his trajectory and to make a contribution to the knowledge of processes of transition to what is known in Mexico as the Restored Republic, as it was expressed locally and, secondarily, to the studyof banditry, clarifying the meaning of the term â€œbanditâ€ in a context characterizedby arm confrontation.